1996
DOI: 10.1128/jb.178.5.1401-1411.1996
|View full text |Cite
|
Sign up to set email alerts
|

Functional analysis of a relA/spoT gene homolog from Streptococcus equisimilis

Abstract: 2We examined the functional attributes of a gene encountered by sequencing the streptokinase gene region of Streptococcus equisimilis H46A. This gene, originally called rel, here termed rel S. equisimilis , is homologous to two related Escherichia coli genes, spoT and relA, that function in the metabolism of guanosine 5,3-polyphosphates [(p)ppGpp]. Studies with a variety of E. coli mutants led us to deduce that the highly expressed rel S. equisimilis gene encodes a strong (p)ppGppase and a weaker (p)ppGpp synt… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

11
127
0

Year Published

1997
1997
2017
2017

Publication Types

Select...
6
3
1

Relationship

0
10

Authors

Journals

citations
Cited by 116 publications
(138 citation statements)
references
References 57 publications
11
127
0
Order By: Relevance
“…In this study, the E. coli RelA/SpoT couple was proposed to act as a toxin/antitoxin system locking cells in a condition of stasis. L. lactis does not possess a SpoT analogRelA exhibits both (p)ppGpp synthesis and degradation activities (16,27). Nevertheless, the stringent response-induced nongrowth state of E. coli and that of Cel − cells of L. lactis appear to have similarities.…”
Section: Discussionmentioning
confidence: 99%
“…In this study, the E. coli RelA/SpoT couple was proposed to act as a toxin/antitoxin system locking cells in a condition of stasis. L. lactis does not possess a SpoT analogRelA exhibits both (p)ppGpp synthesis and degradation activities (16,27). Nevertheless, the stringent response-induced nongrowth state of E. coli and that of Cel − cells of L. lactis appear to have similarities.…”
Section: Discussionmentioning
confidence: 99%
“…Several relA or spoT homologues have been cloned and characterized (Avarbock et al, 1999;Flärdh et al, 1994;Martinez-Costa et al, 1998;Mechold et al, 1996;Ostling et al, 1996;van der Biezen et al, 2000;Wendrich & Marahiel, 1997;Xiao et al, 1991). The induction of relA or spoT homologues is affected by various factors.…”
Section: Discussionmentioning
confidence: 99%
“…The E. coli dGTPase (EC 3.1.5.1) catalyzes the Mg 2ϩ -dependent hydrolysis of dGTP to deoxyguanosine and tripolyphosphate (49,50). The major role of the RelA proteins from E. coli and S. equisimilis is the breakdown of (p)ppGpp by a Mn 2ϩ -dependent (p)ppGpp pyrophosphohydrolase activity (51)(52)(53). Very recently, we demonstrated that the HD domain of the E. coli tRNA-nucleotidyltransferase has 2Ј,3Ј-cyclic phosphodiesterase, 2Ј-nucleotidase, and phosphatase activities (54).…”
Section: Screening Of Purified Proteins For Phosphatase Activity-mentioning
confidence: 99%